2019
DOI: 10.1007/s42773-019-00032-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake, maximum yield production, and economic return of maize under deficit irrigation with biochar and inorganic fertiliser amendments

Abstract: The individual and combined effects of biochar (B) and inorganic fertiliser (F) have all been widely proofed to improve soil fertility and enhance crop growth and yield under irrigation (I) and rain fed conditions. However, the strength of their individual and combined effects on crop productivity has been scarcely reported. In addition, few studies have assessed their individual and co-application effects on economic returns. Therefore, a 2-year field experiment which consisted of factorial combination of irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
(59 reference statements)
2
19
0
Order By: Relevance
“…Thus, increasing the yield or tomato production. This is in line with earlier study that biochar application enhanced crop yield especially maize and tomato (Faloye et al, 2020 andRonga et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, increasing the yield or tomato production. This is in line with earlier study that biochar application enhanced crop yield especially maize and tomato (Faloye et al, 2020 andRonga et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Plethora of studies conducted in varying parts of the globe and on different plants have shown that biochar application/amendment affected soil microbial activities and abundance, improved cationic exchange capacity (CEC), pH, nodulation, soil water holding capacity, nutrient availability/intake and plant productivity (Mulabagal et al, 2015, Palansooriya et al, 2019and Faloye et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Electrometric method was used to determine the soil pH [13]. Available P was determined by Acid Fluoride Extraction procedure (Bray-1 Method) [14].…”
Section: Soil Chemical and Heavy Metal Assessmentmentioning
confidence: 99%
“…Also, a more comprehensive approach was used in the 2017/2018 growing season by determining the physical and chemical properties from the replicates of each fertility plot under each irrigation treatment. The method of soil analysis is reported in our previously published paper (Faloye et al 2020).…”
Section: Field Experimentationmentioning
confidence: 99%